Bridging biodiversity and food systems: A nationwide synthesis of non-conventional food plants (PANCs) in Brazil - Gustavo Barreto Costa; Luiz Henrique Silva Lopes; Karina Pinheiro Martins; Nathália Letícia Hernandez Brito; Jhony Silva Ramos; Ana Caroline Silvestre Barbosa Alessi; Ana Elisa Melo da Silva; Thais Aparecida Santos; Ornella Monique Pereira Ferri; Maria João de Almeida Coelho de Sousa; Sandrina Alves Heleno; Douglas Neil Rutledge; et al. (Agricultural Systems, 2026)

Gold nanoparticles prevent the establishment of severe malaria in a murine animal model - Sarah Aparecida dos Santos Alves; Douglas Esteves Teixeira; Lavínia Reif Correa Oliveira; Maria Eduarda Lopes Souza; Monique Martins Melo; Mayck Medeiros; Sabrina Sodré-Serra; Paticia Machado Rodrigues Silva; Marco Aurélio Martins; Pedro Leme Silva; Patricia Rieken Macedo Rocco; Celso Caruso-Neves; et al. (Journal of Pharmaceutical Investigation, 2026)

Towards environmental management of WEEE in Brazil: evaluating the impacts of recycling plastics - Abner Fernandes Souza da Silva; Guilherme Andreazza de Freitas; Diogo Aparecido Lopes Silva; Jane Maria Faulstich de Paiva; Juliana Mendes Campolina; Virgínia Aparecida da Silva Moris (Environmental Science and Pollution Research, 2026)
Plastic fractions recovered from waste electrical and electronic equipment (WEEE) are growing rapidly worldwide, yet their net environmental benefit remains under-quantified—especially in emerging economies such as Brazil, where recycling infrastructure is still maturing. Acrylonitrile–Butadiene–Styrene (ABS) and High-Impact Polystyrene (HIPS) together account for a large share of this stream and offer high material value if efficiently reprocessed. This study applies ISO 14040/14044 life cycle assessment to quantify the impacts of recycling ABS and HIPS collected from Brazilian WEEE. Foreground data from an industrial plant in Sorocaba were modeled with ReCiPe 2016 midpoint indicators. Extrusion emerged as the dominant hotspot, contributing 75.2% (ABS) and 85.7% (HIPS) of total impacts, whereas transport accounted for < 5%. Cutting extrusion energy by 30% reduced global warming potential (GWP) by 25% for HIPS and 22% for ABS, while switching to Brazil’s renewable-rich grid reduced impacts across the main categories. Compared with virgin resin, recycling resulted in substantially lower global warming impacts for both HIPS and ABS. The sensitivity analysis showed that adopting an economic allocation approach led to lower environmental impacts compared with mass-based allocation for both ABS and HIPS. Optimizing extrusion energy and adopting low-carbon electricity are therefore critical to maximizing the environmental benefits of WEEE-plastic recycling. Beyond technical insights, these results provide evidence to guide public policies that promote recycling infrastructure and energy efficiency, while reinforcing that recycled plastics offer substantially lower environmental burdens compared with virgin resources.

Efficacy of ozone in bifenthrin degradation and its impact on the quality of common beans (Phaseolus vulgaris L.) - Carlos Henrique de Oliveira Paz; Lêda Rita D'Antonino Faroni; Alessandra Aparecida Zinato Rodrigues; Eugénio da Piedade Edmundo Sitoe; Maria Eliana Lopes Ribeiro de Queiroz; Marcus Vinícius de Assis Silva; Ernandes Rodrigues de Alencar; Carollayne Gonçalves Magalhães (Food Control, 2026)

Seed dispersal by bats in naturally restored mining areas of the Eastern Amazon - Vandressa Regina Nunes Henriques; Heitor Antunes de Castro; Thayse Cristine Melo Benathar; Roberta Macedo Cerqueira; Maria Aparecida Lopes; Marlúcia Bonifácio Martins; Leonardo Carreira Trevelin (Food Webs, 2026)

Açaí management intensification impoverishes Amazonian avian assemblages in estuarine forests - Madson Antonio Benjamin Freitas; Raphael Vasconcelos Nunes; Maria Aparecida Lopes; Caio Crisley Moura Soares; Thiago Sanna Freire Silva; Ima Célia Guimarães Vieira; Marcelo Tabarelli; Alexander Charles Lees (Biological Conservation, 2026)

Diet of White-Cheeked Spider Monkeys (Ateles marginatus) in Continuous Forests at the Cristalino Private Reserve (Mato Grosso – Brazil) - Paola Cardias Soares; Gustavo Rodrigues Canale; Maria Aparecida Lopes; Makupa Kayabi; Bruno Castelo Branco Damiani; Leandro Pereira Piva; Liza Maria Veiga (International Journal of Primatology, 2026)

Larvicidal efficacy of Varronia curassavica leaf phytochemicals against Aedes aegypti: anatomical, histological and cytotoxic analyses - Marcela Rezende Cordeiro; Saulo Pireda; Maria Aparecida Aride Bertonceli; Thalya Soares Ribeiro Nogueira; Nicolly Lopes Bautz; Rodrigo Barbosa Braga Feitoza; Felipe Figueirôa Moreira; Ivo José Curcino Vieira; Carlos Roberto Ribeiro Matos; Raimundo Braz-Filho; Sergio Henrique Seabra; Francisco José Alves Lemos; et al. (Pesticide Biochemistry and Physiology, 2026)

Far-red LED light treatment at harvest and during storage to control sprouting in ‘Asterix’ potatoes - Vanessa Maria Dantas Pedrosa; Maiqui Izidoro; Maryelle Barros da Silva; Nathalia Aparecida Barbosa Lossolli; Arthur Bernardes Cecílio Filho; Rogério Falleiros Carvalho; Allan Lopes Bacha; Gustavo Henrique de Almeida Teixeira (Postharvest Biology and Technology, 2025)

A pain from the nose to the head: neurological commitment during long COVID - Laura Cardoso Corrêa-Dias; Ágata Lopes-Ribeiro; Gabriel Eduardo Ribeiro Mendes; Geovane Marques-Ferreira; Caio Wilker-Teixeira; Felipe Alves Clarindo; Victor de Melo Rocha; Maria Eduarda Martuchele-Félix; Henrique Morais Retes; Thaiza Aline Pereira Santos; Gabriela Lorrany Aparecida Azevedo; Verônica Evelyn Viana Pereira; et al. (Inflammation Research, 2025)

Epstein-barr virus (EBV) in cervical carcinoma detected by in situ hybridization targeting ebers and the viral genome - Álife Diêgo Lima Silva; Julia Graziele Alves Marelli; Maria Willaiara Lira Lopes; Myrella Tavares Rodrigues; Cecília Paz Lopes; José Nairton Coelho Silva; Sávio Samuel Feitosa Machado; Racquel Oliveira da Silva Souza; Maria Aparecida Tibúrcio; Alexandre Quental Sampaio; Isabelle Joyce de Lima Silva Fernandes; Claudia do Ó Pessoa; et al. (Brazilian Journal of Microbiology, 2025)

In silico search reveals the association of lichens with black yeast-like fungi in the order Chaetothyriales - Flavia de Fatima Costa; Bruno Paulo Rodrigues Lustosa; Camila Pereira Perico; Ricardo Belmonte-Lopes; João Lucas Vitório Ribeiro Carvalho; Emanuel L. Razzolini; Germana Davila dos Santos; Bruna Jacomel Favoreto de Souza Lima; Cristina Maria de Souza-Motta; Roberto Tadeu Raittz; Yinggai Song; Laura Selbmann; et al. (Fungal Biology, 2025)

Occurrence of aflatoxins in organic rice produced and commercialized in Brazil - Natalia Aparecida Barbosa; Andrezza Maria Fernandes; Leonardo de Oliveira Seno; Maria Fernanda de Castro Burbarelli; Alessandra Lopes de Oliveira; Fernanda Bovo (Food Control, 2024)

Supplying the ethanol demand for 2030 in Brazil as a land-based climate change mitigation alternative: Implications on greenhouse gases emissions - Guilherme Pessoa Nogueira; Gabriel Palma Petrielli; Mateus Ferreira Chagas; Daniele de Souza Henzler; Isabelle Lobo de Mesquita Sampaio; Antonio Maria Bonomi; Tassia Lopes Junqueira; Edvaldo Rodrigo de Morais; Thayse Aparecida Dourado Hernandes (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Soybean oil, linoleic acid source, in lamb diets: carcass traits and meat quality - Victor Guimarães Oliveira Lima; Liliane Oliveira da Silva; José Esler de Freitas Júnior; Henry Daniel Ruiz Alba; Lara Maria Santos Brant; Douglas dos Santos Pina; Bruna Mara Aparecida de Carvalho Mesquita; José Augusto Gomes Azevêdo; Dorgival Morais de Lima Júnior; Maria Leonor Garcia Melo Lopes de Araújo; Gleidson Giordano Pinto de Carvalho (Tropical Animal Health and Production, 2024)

Orbital multispectral imaging: a tool for discriminating management strategies for nematodes in coffee - Vinicius Silva Werneck Orlando; Bruno Sérgio Vieira; George Deroco Martins; Everaldo Antônio Lopes; Gleice Aparecida de Assis; Fernando Vasconcelos Pereira; Maria de Lourdes Bueno Trindade Galo; Leidiane da Silva Rodrigues (Precision Agriculture, 2024)

Melia azedarach L. in vitro plantlets as a new source of antifeeding salannin- and nimbolinin-type limonoids - Daniel Yuri Akiyama; Maria Eduarda Radavelli Santos; Marina Ferreira Maximo; Maria de Fátima das Graças Fernande da Silva; Adriana Aparecida Lopes; Taicia Pacheco Fill (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Liquid-liquid and solid-liquid extractions with low-temperature partitioning – A review - Adilson Correia Goulart; Alessandra Aparecida Zinato Rodrigues; Fernanda Fernandes Heleno; Anizio Marcio de Faria; Simone Machado Goulart; Maria Eliana Lopes Ribeiro de Queiroz (Analytica Chimica Acta, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Comparative genetic and pathogenic approaches of Escherichia coli isolated simultaneously from pyometra and urine of bitches - Cassiane Elisabete Lopes; Tainara Soares Weyh; Camila Azevedo Moni; Maria Eduarda Dias; Tania Aparecida Tardelli Gomes; Mateus Matiuzzi da Costa; Rommel Thiago Jucá Ramos; Aristóteles Góes-Neto; Vasco Ariston de Carvalho Azevedo; Bertram Brenig; Franciele Maboni Siqueira (Veterinary Research Communications, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Correction: Synergism between molecules derived from Garcinia brasiliensis and antimicrobial drugs on field isolates of Mycoplasma hyopneumoniae - Bruna Araújo Euzébio Alves Jacob Lopes; Leonardo Teófilo Toledo; Jéssica Lobo Albuquerque Caldeira; Fábio Assad Feres Rodrigues; Mariana de Barros; Luiz Fernando Lino de Souza; Natália Fialho Gonzaga; Marcelo Henrique dos Santos; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira (Brazilian Journal of Microbiology, 2024)

Synergism between molecules derived from Garcinia brasiliensis and antimicrobial drugs on field isolates of Mycoplasma hyopneumoniae - Bruna Araújo Euzébio Alves Jacob Lopes; Leonardo Teófilo Toledo; Jessica Lobo Albuquerque Caldeira; Fábio Assad Feres Rodrigues; Mariana de Barros; Luiz Fernando Lino de Souza; Natália Fialho Gonzaga; Marcelo Henrique dos Santos; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira (Brazilian Journal of Microbiology, 2024)

Unveiling the structure of Spondias tuberosa dispersal units through X-ray imaging - Allana Mellyse Barbosa Rodrigues; Maria Fernanda Oliveira Torres; Valdinete Viera Nunes; Juliana Lopes Souza; Natali Aparecida Santana; Renata Silva-Mann (Genetic Resources and Crop Evolution, 2024)

Fate and toxicity of 2,4-D and fipronil in mesocosm systems - Bianca Veloso Goulart; Beatriz De Caroli Vizioli; Thandy Junio da Silva Pinto; Juliane Silberschmidt Freitas; Raquel Aparecida Moreira; Laís Conceiçao Menezes da Silva; Maria Paula Cardoso Yoshii; Laís Fernanda de Palma Lopes; Allan Pretti Ogura; Theodore Burdick Henry; Evaldo Luiz Gaeta Espindola; Cassiana Carolina Montagner (Chemosphere, 2024)

Local and landscape factors influencing mercury distribution in water, bottom sediment, and biota from lakes of the Araguaia River floodplain, Central Brazil - Lucas Cabrera Monteiro; Ludgero Cardoso Galli Vieira; José Vicente Elias Bernardi; Wanderley Rodrigues Bastos; João Pedro Rudrigues de Souza; Maria Cristina Nery do Nascimento Recktenvald; Adriely Ferreira da Costa Nery; Iuri Aparecida da Silva Oliveira; Cássio da Silva Cabral; Lilian de Castro Moraes; Cleber Lopes Filomeno; Jurandir Rodrigues de Souza (Science of The Total Environment, 2024)

Multidrug Efflux System-mediated resistance in Staphylococcus aureus under a One Health approach - Mariana de Barros; Ilderlane da Silva Lopes; Ana Júlia Moreira; Raquel dos Santos Oliveira Almeida; Mateus Matiuzzi da Costa; Rinaldo Aparecido Mota; Luis Augusto Nero; Maria Aparecida Scatamburlo Moreira (World Journal of Microbiology and Biotechnology, 2024)

Dry heat whole Sorghum BRS 305 flour modulate satiety and improves antioxidant response in brain of Wistar rats fed with high-fat high-fructose diet - Haira Guedes Lúcio; Mariana Grancieri; Oscar David Medina Martinez; Renata Celi Lopes Toledo; Cícero Beserra de Menezes; Neuza Maria Brunoro Costa; Valéria Aparecida Vieira Queiroz; Bárbara Pereira da Silva; Hércia Stampini Duarte Martino (Food Research International, 2023)

Sweet sorghum (Sorghum bicolor (L.) Moench) molasses: Physicochemical characterization and in vitro bioavailability of different genotypes - Andressa de Assis; Bárbara Pereira da Silva; Renata Celi Lopes Toledo; Rafael Augusto da Costa Parrella; Raymond P. Glahn; Izabela Maria Montezano de Carvalho; Valéria Aparecida Vieira Queiroz; Hercia Stampini Duarte Martino (Journal of Cereal Science, 2023)

Evaluation of imazalil dissipation/migration in postharvest papaya using low-temperature partition extraction and GC–MS analysis - Jéssika Faêda de Freitas; Maria Eliana Lopes Ribeiro de Queiroz; André Fernando de Oliveira; Leandro de Paulo Ribeiro; Davi Vittorazzi Salvador; Liany Divina Lima Miranda; Robson Ribeiro Alves; Alessandra Aparecida Zinato Rodrigues (Food Chemistry, 2023)

From enzyme to cell-factory: Economic and environmental assessment of biobased pathways to unlock the potential of long-haul transportation biofuels - Mateus Ferreira Chagas; Gabriela Filipini Ferreira; Luísa Clemente Magalhães Gomes; Leticia Maria Zanphorlin; Liliana Zanelli Oliveira Martins; Isabelle Lobo Mesquita Sampaio; Thayse Aparecida Dourado Hernandes; Tassia Lopes Junqueira; Edvaldo Rodrigo Morais (Chemical Engineering Journal, 2023)

New, fast, and precise method of COVID-19 detection in nasopharyngeal and tracheal aspirate samples combining optical spectroscopy and machine learning - Denny M. Ceccon; Paulo Henrique R. Amaral; Lídia M. Andrade; Maria I. N. da Silva; Luis A. F. Andrade; Thais F. S. Moraes; Flavia F. Bagno; Raissa P. Rocha; Daisymara Priscila de Almeida Marques; Geovane Marques Ferreira; Alice Aparecida Lourenço; Ágata Lopes Ribeiro; et al. (Brazilian Journal of Microbiology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Responses of Chironomus sancticaroli to the simulation of environmental contamination by sugarcane management practices: Water and sediment toxicity - Thandy Junio da Silva Pinto; Raquel Aparecida Moreira; Juliane Silber schmidt Freitas; Laís Conceição Menezes da Silva; Maria Paula Cardoso Yoshii; Laís Fernanda de Palma Lopes; Allan Pretti Ogura; Gabriele Verônica de Mello Gabriel; Luana Maria Tavares Rosa; Luis Schiesari; Janaina Braga do Carmo; Cassiana Carolina Montagner; et al. (Science of The Total Environment, 2023)

Correlation Between Drinking Water and Iodine Status: a Systematic Review and Meta-analysis - Francilene Maria Azevedo; Almeida Abudo Leite Machamba; Aline Carare Candido; Carina Aparecida Pinto; Sílvia Oliveira Lopes; Mariana de Souza Macedo; Sarah Aparecida Vieira Ribeiro; Silvia Eloiza Priore; Sylvia do Carmo Castro Franceschini (Biological Trace Element Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Cacti as low-cost substrates to produce L-asparaginase by endophytic fungi - Leticia Francisca da Silva; Ana Patrícia Sousa Lopes de Pádua; Layanne de Oliveira Ferro; Gualberto Segundo Agamez-Montalvo; Jadson Diogo Pereira Bezerra; Keila Aparecida Moreira; Cristina Maria de Souza-Motta (World Journal of Microbiology and Biotechnology, 2022)

What are the main environmental predictors of differences in the community structure of periphytic desmids in a semi-arid floodplain lake? - Maria Aparecida dos Santos; Carla Ferragut; Nadson Ressyé Simões; Daniela Mariano Lopes da Silva; Carlos Wallace do Nascimento Moura (Aquatic Ecology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Irrigation with Water Contaminated by Sugarcane Pesticides and Vinasse Can Inhibit Seed Germination and Crops Initial Growth - Allan Pretti Ogura; Raquel Aparecida Moreira; Laís Conceição Menezes da Silva; Giovana Spinelli Negro; Juliane Silberschmidt Freitas; Thandy Junio da Silva Pinto; Laís Fernanda de Palma Lopes; Maria Paula Cardoso Yoshii; Bianca Veloso Goulart; Cassiana Carolina Montagner; Evaldo Luiz Gaeta Espíndola (Archives of Environmental Contamination and Toxicology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Antibiotic Followed by a Potential Probiotic Increases Brown Adipose Tissue, Reduces Biometric Measurements, and Changes Intestinal Microbiota Phyla in Obesity - Mariana de Moura e Dias; Sandra Aparecida dos Reis Louzano; Lisiane Lopes da Conceição; Rayssa da Conceição Fernandes; Tiago Antônio de Oliveira Mendes; Solange Silveira Pereira; Leandro Licursi de Oliveira; Maria do Carmo Gouveia Peluzio (Probiotics and Antimicrobial Proteins, 2021)

Soybean drought-stressed plants impair Anticarsia gemmatalis (Lepidoptera: Erebidae) midgut proteolytic activity and survival - Verônica Aparecida Faustino; Rafael de Almeida Barros; Neilier Rodrigues da Silva Júnior; Samuel Lessa Barbosa; Camilo Elber Vital; Felipe Lopes da Silva; Yaremis Beatriz Meriño Cabrera; Wellington Garcia Campos; Humberto Josué de Oliveira Ramos; Maria Goreti de Almeida Oliveira (Phytoparasitica, 2021)

Multimarker approach to assess the exposure of the wild rodent Calomys laucha to a simulated crude oil spill - Krissia Aparecida de Almeida; Edariane Menestrino Garcia; Julia Oliveira Penteado; Ronan Adler Tavella; Caroline Lopes Feijo Fernandes; Paula Florencio Ramires; Osmar Vieira Ramires Júnior; Ana Luíza Muccillo-Baisch; Maria da Luz Mathias; Deodália Dias; Flavio Manoel Rodrigues da Siva Júnior (Environmental Science and Pollution Research, 2021)

Liquid crystalline nanodispersion functionalized with cell-penetrating peptides improves skin penetration and anti-inflammatory effect of lipoic acid after in vivo skin exposure to UVB radiation - Patrícia Mazureki Campos; Fabíola Garcia Praça; Samuel Vidal Mussi; Sônia Aparecida Figueiredo; Márcia Carvalho de Abreu Fantini; Maria José Vieira Fonseca; Vladimir P. Torchilin; Maria Vitória Lopes Badra Bentley (Drug Delivery and Translational Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Phytotoxicity and cytogenotoxicity of composted tannery sludge - Matheus de Moraes Cunha Gonçalves; Angela Celis de Almeida Lopes; Regina Lucia Ferreira Gomes; Wanderley José de Melo; Ademir Sergio Ferreira Araujo; José Baldin Pinheiro; Maria Aparecida Marin-Morales (Environmental Science and Pollution Research, 2020)

Antimicrobial susceptibility and genetic profile of Mycoplasma hyopneumoniae isolates from Brazil - Natália Fialho Gonzaga; Luiz Fernando Lino de Souza; Marcus Rebouças Santos; Viviane Sisdelli Assao; Andrew Rycroft; Alannah Saskia Deeney; Juliana Lopes Rangel Fietto; Gustavo Costa Bressan; Maria Aparecida Scatamburlo Moreira; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2020)

The challenge of determining the impact of FUT3 tumor-associated polymorphism rs2306969 (-6951 C> T) in invasive breast cancer cells - Jessica Catarine Frutuoso do Nascimento; Anderson de Oliveira Vasconcelos; Maria Aparecida Barreto Lopes Seabra; Eduardo Isidoro Carneiro Beltrão; Cíntia Renata Costa Rocha (Molecular Biology Reports, 2019)

Comparative study of phytotoxicity and genotoxicity of soil contaminated with biodiesel, diesel fuel and petroleum - Jaqueline Matos Cruz; Nádia Aline Corroqué; Renato Nallin Montagnoli; Paulo Renato Matos Lopes; Maria Aparecida Marin Morales; Ederio Dino Bidoia (Ecotoxicology, 2019)

Bioaccumulation Study of Produced Water Discharges from Southeastern Brazilian Offshore Petroleum Industry Using Feral Fishes - Rafael André Lourenço; Eleine Francioni; Antonio Henrique M. F. T. da Silva; Caio Augusto Magalhães; Fabiana Dias Costa Gallotta; Fabio Francisco de Oliveira; João Maximino de Souza; Leandro Franco Macena de Araújo; Liliane Pequeno de Araújo; Marcus Antonio G. de Araújo Júnior; Maria de Fátima Guadalupe Meniconi; Monica Aparecida Ferreira de Souza Bindes Gomes Lopes (Archives of Environmental Contamination and Toxicology, 2018)

Nitrogen distribution in a tropical urbanized estuarine system in northeastern Brazil - Celimarcos Bezerra dos Santos; Maria Aparecida Macêdo Silva; Marcelo F. Landim de Souza; Daniela Mariano Lopes da Silva (Environmental Monitoring and Assessment, 2018)

Genotoxicity in adult residents in mineral coal region—a cross-sectional study - Edlaine Acosta Da Silva Pinto; Edariane Menestrino Garcia; Krissia Aparecida de Almeida; Caroline Feijó Lopes Fernandes; Ronan Adler Tavella; Maria Cristina Flores Soares; Paulo Roberto Martins Baisch; Ana Luíza Muccillo-Baisch; Flavio Manoel Rodrigues da Silva Júnior (Environmental Science and Pollution Research, 2017)

Reassessment of the taxonomic position of Burkholderia andropogonis and description of Robbsia andropogonis gen. nov., comb. nov. - Lucilene Lopes-Santos; Daniel Bedo Assumpção Castro; Mariana Ferreira-Tonin; Daniele Bussioli Alves Corrêa; Bevan Simon Weir; Duckchul Park; Laura Maria Mariscal Ottoboni; Júlio Rodrigues Neto; Suzete Aparecida Lanza Destéfano (Antonie van Leeuwenhoek, 2017)

Distribution of infectious bronchitis virus strains in different organs and evidence of vertical transmission in natural infection - Claiton Gonçalves Pereira; Giuliana Loreto Saraiva; Pedro Marcus Pereira Vidigal; Juliana Lopes Rangel Fietto; Gustavo Costa Bressan; Maria Aparecida Scatamburlo Moreira; Márcia Rogéria de Almeida; Abelardo Silva Júnior (Archives of Virology, 2016)

Liver Biomarkers and Their Applications to Nutritional Interventions in Animal Studies - Cynthia Aparecida de Castro; Manoela Maciel dos Santos Dias; Karina Ana da Silva; Sandra Aparecida dos Reis; Lisiane Lopes da Conceição; Letícia De Nadai Marcon; Luis Fernando de Sousa Moraes; Maria do Carmo Gouveia Peluzio (Exposure and Health, 2015)

PCR as a Screening Test for Invasive Aspergillosis in Haematological Patients: A Pilot Study - Thomas Victor Maciel da Silva; Lilian Carla Carneiro; Francine dos Santos Ramos; Ludmila Fiorenzano Baethgen; Alessandra Aparecida Paz; Daniela Zilio Larentis; Liane Esteves Daudt; Cintia Tusset; Leila Maria Lopes-Bezerra; Alessandro C. Pasqualotto (Mycopathologia, 2014)

Leguminous plants nodulated by selected strains of Cupriavidus necator grow in heavy metal contaminated soils amended with calcium silicate - Paulo Ademar Avelar Ferreira; Guilherme Lopes; Cleide Aparecida Bomfeti; Silvia Maria de Oliveira Longatti; Cláudio Roberto Fonseca de Sousa Soares; Luiz Roberto Guimarães Guilherme; Fatima Maria de Souza Moreira (World Journal of Microbiology and Biotechnology, 2013)

Activity budget, diet, and use of space by two groups of squirrel monkeys (Saimiri sciureus) in eastern Amazonia - Tatyana Pinheiro; Stephen F. Ferrari; Maria Aparecida Lopes (Primates, 2013)

CXCL12 and TP53 genetic polymorphisms as markers of susceptibility in a Brazilian children population with acute lymphoblastic leukemia (ALL) - Aparecida de Lourdes Perim; Roberta Losi Guembarovski; Julie Massayo Maeda Oda; Leandra Fiori Lopes; Carolina Batista Ariza; Marla Karine Amarante; Maria Helena Pelegrinelli Fungaro; Karen Brajão de Oliveira; Maria Angelica Ehara Watanabe (Molecular Biology Reports, 2013)

Global environmental changes: setting priorities for Latin American coastal habitats - Alexander Turra; Aldo Cróquer; Alvar Carranza; Andrés Mansilla; Arsenio J. Areces; Camilo Werlinger; Carlos Martínez‐Bayón; Cristina Aparecida Gomes Nassar; Estela Plastino; Evangelina Schwindt; Fabrizio Scarabino; Fungyi Chow; et al. (Global Change Biology, 2013)
As the effects of the Global Climate Changes on the costal regions of Central and South Americas advance, there is proportionally little research being made to understand such impacts. This commentary puts forward a series of propositions of strategies to improve performance of Central and South American science and policy making in order to cope with the future impacts of the Global Climate Changes in their coastal habitats.

The interference of cold ischemia time in the quality of total RNA from frozen tumor samples - Cristiano Ribeiro Viana; Cristovam Scapulatempo Neto; Ligia Maria Kerr; Edenir Inêz Palmero; Marcia Maria Chiquitelli Marques; Tamara Colaiacovo; Abel Feliciano de Queiroz Junior; André Lopes Carvalho; Sheila Aparecida Coelho Siqueira (Cell and Tissue Banking, 2013)

Diversity of use and local knowledge of palms (Arecaceae) in eastern Amazonia - Fábio Ribeiro Araújo; Maria Aparecida Lopes (Biodiversity and Conservation, 2012)

In vitro activity of compounds isolated from Piper crassinervium against Trypanosoma cruzi - Adriana Aparecida Lopes; Silvia Noelí López; Luis Octávio Regasini; João Marcos Batista Junior; Daniela Luz Ambrósio; Massuo Jorge Kato; Vanderlan da Silva Bolzani; Regina Maria Barretto Cicarelli; Maysa Furlan (Natural Product Research, 2008)

A lyophilized aqueous extract of Maytenus ilicifolia leaves inhibits histamine-mediated acid secretion in isolated frog gastric mucosa - Patrícia Maria Ferreira; César Nonato de Oliveira; Alaide Braga de Oliveira; Miguel José Lopes; Fernando Alzamora; Maria Aparecida Ribeiro Vieira (Planta, 2004)